REALITIES AND PROSPECTS FOR PHARMACOLOGICAL CORRECTION OF «ADMA-ENOS"-ASSOCIATED WAYS IN PREECLAMPSIA - M. V. Pokrovsky (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2016)
Methylated analogs of L-arginine - asymmetric dimetilarginin (ADMA) and monometilarginin (L-NMMA) - are endogenous inhibitors of endothelial NO-synthase (eNOS). ADMA level in maternal plasma is increased in women with preeclampsia. The high level of ADMA is one of the predictors of preeclampsia. L-arginine increases the activity of eNOS and production of nitric oxide in the ADMA-similar model of L-NAME-induced endothelial dysfunction. ENOS activator (resveratrol), antioxidants, potentiated polyclonal antibodies to eNOS and others agents have been effective in this model. Studies of endotelioprotective activity in other «ADMA-eNOS-associated" experimental models of metabolic syndrome and homocysteine-induced, gipoestrogen-induced sepsis-induced endothelial dysfunction and endothelial dysfunction in postvaccinal vasculitis have been developed.